Body mass index and hand osteoarthritis susceptibility: an updated meta‐analysis. (5th November 2016) - Jiang, Liying; Xie, Xiaohua; Wang, Yidan; Wang, Yingchen; Lu, Yihua; Tian, Tian; Chu, Minjie; Shen, Yi
Abstract: Aim: Numerous epidemiologic studies have evaluated the association between overweight and hand osteoarthritis; However, the existing results are inconsistent. Methods: Systematic searches were performed and reference lists from the retrieved trials were searched. This meta‐analysis and meta‐regression was executed to identify all English‐language articles that quantitatively assess the strength of associations between body mass index and hand osteoarthritis risk. Study‐specific incremental estimates were standardized to determine the risk associated with a 5 kg/m 2 increase in body mass index. We conducted the study according to the guidelines for the meta‐analysis of observational studies in epidemiology. Results: Of the 21 studies included, 13 were cross‐sectional studies, three were case control studies and five were cohort studies. The pooled summary estimates were 1.10 (95%CI: 0.98–1.24) with no significant difference ( P = 0.09). Subgroup analysis shows that body mass index was positively associated with hand osteoarthritis in cross‐sectional studies (1.05 [95%CI: 1.02–1.08] P < 0.01), while with no significant difference was found in case‐control studies (1.28 [95%CI: 0.87–1.88]) and in cohort studies (1.06 [95%CI: 0.71–1.58]) ( P = 0.21 and P = 0.77, respectively). A weak but significant effect on radiographic hand osteoarthritis risk was found. The summary estimates were 1.06 (95%CI: 1.02–1.10) in studies defined by radiography and 1.25 (95%CI: 1.06–1.49) by radiography and clinically ( P < 0 .01 and P = 0.01, respectively). Conclusion: It appears that increased body mass index contributes to a positively moderate effect on susceptibility to hand osteoarthritis, as defined radiographically and/or radiographically and clinically. The effects vary by study design and osteoarthritis definition.